2015
DOI: 10.2527/jas.2014-8406
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of monensin and Optimase to beef cows consuming low-quality forage during late gestation and early lactation

Abstract: Two experiments were designed to investigate the effects of feeding monensin and/or slow release urea with a fibrolytic feed enzyme (Optimase; Alltech, Inc., Nicholasville, KY) on performance, milk production, calf growth performance, and blood metabolites in beef cows. Spring-calving cows and heifers were used in a completely randomized design in Exp. 1 (N = 84; 534 ± 68 kg initial BW) and Exp. 2 (N = 107; 508 ± 72 kg initial BW). Exp. 1 supplements were formulated to meet cow protein requirements and fed dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…However, these effects were not observed in the current study; inclusion of monensin did not affect cow BW change over the 56-d trial, nor did it affect measures of fat deposition or RE. Linneen et al (2015) did not observe changes in cow BW or condition score due to monensin supplementation in beef cows, while Walker et al (1980) reported 3.4% to 11.7% decreases in feed required for BW stasis in pregnant cows fed monensin, suggesting improved diet utilization or energy yield.…”
Section: Discussionmentioning
confidence: 69%
“…However, these effects were not observed in the current study; inclusion of monensin did not affect cow BW change over the 56-d trial, nor did it affect measures of fat deposition or RE. Linneen et al (2015) did not observe changes in cow BW or condition score due to monensin supplementation in beef cows, while Walker et al (1980) reported 3.4% to 11.7% decreases in feed required for BW stasis in pregnant cows fed monensin, suggesting improved diet utilization or energy yield.…”
Section: Discussionmentioning
confidence: 69%
“…Conversely, BW and BCS change was positively influenced by monensin supplementation to gestating cows in the second experiment in Linneen et al. (2015).…”
Section: Resultsmentioning
confidence: 95%
“…Experiment one in Linneen et al. (2015) showed no influence of monensin on BW or BCS change of lactating cows. In more dated research, the first experiment in Lemenager, Owens, and Totusek (1978) and Turner et al.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Feeding monensin to grazing beef cows did not affect BCS change in experiment 1, however differences between days were observed, and founding higher scores on day 80 of the experiment. In previous literature, cows consuming monensin during gestation had decreased forage intake, accompanied by either an improvement (Sexten, 2011) or no change in cow gain (Linneen et al, 2015). Bretschneider et al (2008) reported an increase in average daily gain of 12.1% for growing cattle consuming monensin when comparing 46 experiments in a review on the effects of feeding grazing cattle monensin.…”
Section: Discussionmentioning
confidence: 94%